ID 370 – Impaired central processing in pain perception in a patient with insensitivity to pain; evaluation by laser-evoked potential and pain PET. Issue 3 (March 2016) - Kinoshita, M.; Murase, N.; Sawamoto, N.; Endo, T.; Kawamura, M.; Kanda, M.; Fukuyama, H.; Shibasaki, H.; Takahashi, R.; Ikeda, A.
Abstract : Objective: To investigate processes in pain perception and pathophysiology of insensitivity to pain by using laser-evoked potential (LEP) and positron emission tomography during painful stimulation (pain PET). Methods: We investigated a 29-year-old male patient with familial spastic paraparesis who developed insensitivity to pain around 15-year-old. He was mentally retarded but not autistic or depressive. We recorded LEP and regional cerebral blood flow using pain PET of the patient during selective painful stimulation to left hand dorsum delivered by a CO2 laser. Results: The patient described that he could feel the painful stimulation as being touched but they were not painful or hot, while his skin showed burn. LEP elicited cortical potential negative peak latency of 240–284 ms maximum in Cz in normal amplitude and latency. Pain PET evoked activation in the right parietal operculum and posterior insula, the left insula, and bilateral parietal lobes, however, prefrontal area and anterior cingulate cortex were not activated. Conclusions: The current investigation suggests that insensitivity to pain in this patient can be caused by abnormal processing of pain perception in brain. Key message: Insensitivity to pain can be attributed to not only peripheral nerve but also brain.